Altered Gut Microbiome and Fecal Immune Phenotype in Early Preterm Infants With Leaky Gut - Lemme-Dumit, Jose M.; Song, Yang; Lwin, Hnin Wai; Hernandez-Chavez, Claudia; Sundararajan, Sripriya; Viscardi, Rose M.; Ravel, Jacques; Pasetti, Marcela F.; Ma, Bing (Frontiers in Immunology, 2022)
Intestinal barrier immaturity, or "leaky gut," is the proximate cause of susceptibility to necrotizing enterocolitis in preterm neonates. Exacerbated intestinal immune responses, gut microbiota dysbiosis, and heightened barrier injury are considered primary triggers of aberrant intestinal maturation in early life. Inordinate host immunity contributes to this process, but the precise elements remain largely uncharacterized, leaving a significant knowledge gap in the biological underpinnings of gut maturation. In this study, we investigated the fecal cytokine profile and gut microbiota in a cohort of 40 early preterm infants <33-weeks-gestation to identify immune markers of intestinal barrier maturation. Three distinct microbiota types were demonstrated to be differentially associated with intestinal permeability (IP), maternal breastmilk feeding, and immunological profiles. The Staphylococcus epidermidis- and Enterobacteriaceae-predominant microbiota types were associated with an elevated IP, reduced breastmilk feeding, and less defined fecal cytokine profile. On the other hand, a lower IP was associated with increased levels of fecal IL-1alpha/beta and a microbiota type that included a wide array of anaerobes with expanded fermentative capacity. Our study demonstrated the critical role of both immunological and microbiological factors in the early development of intestinal barrier that collectively shape the intestinal microenvironment influencing gut homeostasis and postnatal intestinal maturation in early preterm newborns.